Niclosamide as a chemical probe for analyzing SARS-CoV-2 modulation of host cell lipid metabolism - Garrett, Timothy J.; Coatsworth, Heather; Mahmud, Iqbal; Hamerly, Timothy; Stephenson, Caroline J.; Ayers, Jasmine B.; Yazd, Hoda S.; Miller, Megan R.; Lednicky, John A.; Dinglasan, Rhoel R. (Frontiers in Microbiology, 2023)
SARS-CoV-2 subverts host cell processes to facilitate rapid replication and dissemination, and this leads to pathological inflammation. We used niclosamide (NIC), a poorly soluble anti-helminth drug identified for repurposed treatment of COVID-19, which activates the cells' autophagic and lipophagic processes as a chemical probe to determine if it can modulate the host cell's total lipid profile that would otherwise be either amplified or reduced during SARS-CoV-2 infection. Through parallel lipidomic and transcriptomic analyses we observed massive reorganization of lipid profiles of SARS-CoV-2 infected Vero E6 cells, especially with triglycerides, which were elevated early during virus replication, but decreased thereafter, as well as plasmalogens, which were elevated at later timepoints during virus replication, but were also elevated under normal cell growth. These findings suggested a complex interplay of lipid profile reorganization involving plasmalogen metabolism. We also observed that NIC treatment of both low and high viral loads does not affect virus entry. Instead, NIC treatment reduced the abundance of plasmalogens, diacylglycerides, and ceramides, which we found elevated during virus infection in the absence of NIC, resulting in a significant reduction in the production of infectious virions. Unexpectedly, at higher viral loads, NIC treatment also resulted in elevated triglyceride levels, and induced significant changes in phospholipid metabolism. We posit that future screens of approved drugs should prioritize compounds that effectively counter SARS-CoV-2 subversion of lipid metabolism, thereby reducing virus replication, egress, and the subsequent regulation of key lipid mediators of pathological inflammation.